If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 = r + (-26) -33 = r + -26 Reorder the terms: -33 = -26 + r Solving -33 = -26 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -33 + -1r = -26 + r + -1r Combine like terms: r + -1r = 0 -33 + -1r = -26 + 0 -33 + -1r = -26 Add '33' to each side of the equation. -33 + 33 + -1r = -26 + 33 Combine like terms: -33 + 33 = 0 0 + -1r = -26 + 33 -1r = -26 + 33 Combine like terms: -26 + 33 = 7 -1r = 7 Divide each side by '-1'. r = -7 Simplifying r = -7
| (-5)+(9)= | | 14xy-7x^2+5x=0 | | x^2+10x+17=y | | (4x-2y)+70=180 | | 67=13+u | | 25c=675 | | (3m+6n)(7m+2n)= | | X+(x-10)=90 | | -8*+30=10 | | X^2+3x=13 | | x^2+10x+23=y | | 57+4=s | | x^2+34x+c=0 | | 0=(-16t^2)+30t+3 | | 4x-5x+15=-4+3x+3 | | 3(y-1)-7=-2(-8y+3)-7y | | 6k-8k-9k=7 | | 8x+2-10= | | 5x-1+2x+3=12 | | 8n-(6n+7)=5 | | 13+n-20=xy | | 100x^3-64y^2x= | | 60=10v | | 3h-2m*2h+m= | | 2x^3-2x^2+3x=0 | | 4(u-2)=4u+6-2(-5u-2) | | 70=9x+18+4x | | 3+9w=10 | | -7x-3x-2=-8-8 | | z^3-4z^2+2z+28=0 | | 8x-4+0.33=6x+12 | | 150-40x+3x^2=0 |